Immunometabolic crosstalk between tumor- associated macrophages and ferroptotic cancer cells: mechanisms, regulation, and therapeutic applications - Qian, Zixing; Zhang, Zhuo; Bai, Wei; Li, Jiaxuan; Rao, Xianjun; Huang, Guodong; Liu, Jiabao; Wei, Wei (Frontiers in Immunology, 2026)
Tumor-associated macrophages (TAMs) are central regulators of the metabolic and immunological landscape of solid tumors and are increasingly recognized as key determinants of cancer-cell susceptibility to ferroptosis. Ferroptosis, an iron-dependent form of regulated cell death characterized by lipid peroxidation, is tightly shaped by metabolic cues within the tumor microenvironment (TME). TAMs, through their remarkable metabolic plasticity, modulate iron flux, redox balance, polyunsaturated fatty-acid (PUFA) availability, and glutathione-dependent antioxidant pathways, each of which directly influences ferroptotic vulnerability in neighboring tumor cells. In this review, we synthesize current evidence linking TAM polarization states to the regulation of ferroptosis-related processes, including lipid remodeling, cystokine metabolism, reactive oxygen species (ROS) buffering, and immunometabolic signaling. We further discuss how TAM-derived cytokines, lipid mediators, and iron-handling proteins orchestrate a microenvironment that either promotes or restrains ferroptotic cell death. Finally, we highlight emerging therapeutic strategies aimed at rewiring TAM metabolism or exploiting ferroptosis to overcome immune suppression and therapy resistance. By integrating immunological and metabolic dimensions, this review provides a framework for understanding TAM-ferroptosis crosstalk and its implications for precision immunotherapy in cancer.